Examination of the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) validity and substantive scales in patients with electrical injury. Issue 8 (17th November 2019) - Soble, Jason R.; Resch, Zachary J.; Schulze, Evan T.; Paxton, Jessica L.; Cation, Bailey; Friedhoff, Claire; Costin, Colleen; Fink, Joseph W.; Lee, Raphael C.; Pliskin, Neil H.
Abstract: Objective: Electrical injury (EI) is a distinct subtype of traumatic injury that often results in a unique constellation of cognitive sequelae and unusual sensory experiences due to peripheral nervous system injury that are uncommon in general medical/neurological populations and have been unexplored with the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF). Method: This study examined performance patterns on MMPI-2-RF validity and substantive scales among 62 EI patients who underwent neuropsychological evaluation, of which 46 demonstrated valid symptom reporting and neurocognitive test performance via multiple independent validity indicators and were retained for analysis. Results: Valid EI patients scored significantly higher than the MMPI-2-RF normative sample on several validity scales with the largest effect sizes on F-r (Infrequent Responses), Fs (Infrequent Somatic Responses), FBS-r (Symptom Validity), and RBS (Response Bias), and ≥33% obtaining elevated scores on these scales per standard interpretive criteria. Review of item content on these scales revealed several reflect disturbances in sensation, physical functioning, and/or cognition that are not infrequent in this population. Further, MMPI-2-RF clinical profiles did not reveal generalized distress or noncredible over-reporting. Rather, similar to the MMPI-2, valid EI patients had a specific pattern related to physical/sensory symptoms and reduced positive emotions with elevations on restructured clinical (RC) scale 1 (somatic complaints), somatic/cognitive specific problem scales, and low positive emotions (RC2). Conclusions: Elevations on some MMPI-2-RF validity scale may capture some degree of actual EI sequela that neuropsychologists need to consider to prevent erroneously concluding that a credible EI patient is over-reporting when s/he is reporting bona fide, EI-related symptoms.